PRODUCTIVE ACTION OF DIFFERENT FAT LEVELS IN DIETS OF BULL-CALVES - Petrov Oleg Yuriyevich; Baimukanov Dastanbek Asylbekovich; Tyurin Vladimir Grigoryevich; Semenov Vladimir; Kuzmina Nadezhda Nikolaevna; Nesipbayeva Aigul Kadirovna; Zhylkyshybayeva Meruert Malikovna; Yerezhepova Makpal Shamakhanovna; Apeev Kuanysh Bolatbekovich (Scientific Journal of Pedagogy and Economics, 2019)
One of the important factors determining the quality of animal origin products is the conditions of their production. Meat productivity of animals is directly affected by their full feeding, providing the body with all the necessary nutrients. Lipids are crucial in the full feeding of animals. However, many issues of lipid nutrition of young cattle during fattening associated with its impact on product quality are not yet sufficiently disclosed. In this regard, studies were conducted in which the effect of increasing the fat level in the diets of fattening bull-calves on their meat productivity and a number of qualitative indicators of beef and some products of slaughter was studied. Sunflower oil additives to the level of 4 and 5% (II and III groups) were input in reliance on the dry matter in the diets of fattening bull-calves. The control was the first group of animals, which received the usual economic diets with a fat content of 3% of dry matter. Different investigations have shown that an increase in the fat level in the diets of fattening young bulls had a positive effect on meat productivity, contributed to an enhancing the intensity of their growth, improving slaughter indicators, chemical composition and some functional and technological properties of beef and physicochemical parameters of adipose tissue. Improvement of the fat level in diets contributed to an increase in the intensity of lipid and protein metabolism processes, which characterize strengthening of assimilation processes in the body of young stock, which is consistent with an increase in their live weight gain. In this respect, the obtained results indicate that bull-calves fed with a diet with a 5% of fat content in terms of dry matter had higher meat productivity. The beef obtained from them was characterized by the best quality indicators, that made it possible to consider this fat level as optimal.